ANALISIS KESULITAN BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI SMA PEMBANGUNAN LABORATORIUM UNP - Gusman Hidayat (Jurnal Edukasi dan Penelitian Matematika, 2021)
This study aims to identify the difficulties of class XI MIA SMA Pembangunan Lab.UNP on the derivative of algebraic functions and their causal factors. This type of research is descriptive with a qualitative approach. The data in this study are data from tests, questionnaires and interviews. The Data was analyzed using qualitative, analysis techniques, namely data reduction, data display, and conclusion. The conclusion from the research results are: 1) The difficulties in the material of derivatives of algebraic functions KD 3.8 and 4.8 are difficulties in using the concept of limits to determine derivatives, derivative properties, chain rules, nth derivatives and principles. derivatives in solving problems, 2).The factors that cause students to have difficulty learning mathematics are 1) Internal factors, namely: a) low mathematical talent, b) less effective study habits, c) poor perception of mathematics, 2) external factors, namely: a) the influence of friends b) how to teach the teacher. Keywords— Difficulty, Derivative.